EFEKTIVITAS KEPEMIMPINAN PEREMPUAN DALAM MENINGKATKAN BUDAYA SEKOLAH KOLABORATIF DI SMP - Ruhama, Ruhama; Rizki, Sari; Marsithah, Iis (Research and Development Journal of Education, 2024)
This study aims to explore: 1) The effectiveness of female leadership as a "Mother" in enhancing a collaborative school culture; 2) The effectiveness of female leadership as a "Seductress" in enhancing a collaborative school culture; 3) The effectiveness of female leadership as a "Pet" in enhancing a collaborative school culture; 4) The effectiveness of female leadership as an "Iron Maiden" in enhancing a collaborative school culture. This research uses a Mixed Method Research approach. The qualitative research is based on the philosophy of post-positivism or interpretative methods. The population consists of 161 teachers in secondary schools in Central Aceh Regency, while the sample includes 115 teachers. Quantitative data collection was conducted using a questionnaire. The study took place in secondary schools in Central Aceh Regency over eight months, from October 2023 to May 2024. The results show that the four characteristics of female leadership; (1) nurturing and protective, (2) friendly and communicative, (3) gentle and affectionate, and (4) firm and independent are effective in creating and enhancing a collaborative school culture. Leadership styles that are firm and independent have the most significant impact (63.8%) compared to the other three styles: nurturing and protective (50.5%), gentle and affectionate (49.4%), and friendly and communicative (47.9%). It is recommended that the Central Aceh Regency Education Office provides equal opportunities for female teachers to become school principals, especially considering the relatively low involvement of female teachers in educational leadership in the region.